Analisis Yuridis terhadap Perbuatan Melawan Hukum dalam Sengketa Hak Kepemilikan Tanah Adat dan Perusakan Simbol Adat: (Studi Putusan Mahkamah Agung Nomor 435 K/Pdt/2021) - Marina All Bright Br.Hombing; Rosnidar Sembiring; Maria (CV Rewang Rencang, 2025)
Indigenous land disputes in Indonesia reflect the complexity of the relationship between national and customary legal systems that have not been fully integrated in resolving ownership conflicts. This research employs a normative juridical method to analyze the characteristics of customary land law, legal protection, and unlawful acts in indigenous land disputes in Huta Lumban Gambiri. The research findings indicate that Batak Toba customary land law is communal-spiritual in nature with ownership based on patrilineal lineage through customary symbols such as the Hariara tree, yet faces challenges from legal system dualism. Supreme Court Decision No. 435 K/Pdt/2021 acknowledges the legitimacy of customary rights and historical evidence from Register De Kampoengs, but rejects compensation for the destruction of the Hariara tree, reflecting a lack of understanding of the concept of immaterial loss in customary law.